Food production versus population from food security perspective - Andreea Ion Raluca; Ionut Laurentiu Petre (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The food-population ratio has two determinants: population and agricultural production. The population is constantly growing, putting pressure on existing resources, which are becoming insufficient. Globally, agricultural production has grown at the same rate as population growth, but at different rates in different geographical areas and regions. This raises the question of comparing the rate of growth of agricultural production with the rate of population growth and identifying regions where agricultural production is growing compared with regions where population growth is occurring.
Keywords: Q18; Q56; 330; Food-population ratio; food security; population growth; agricultural production